2022
DOI: 10.3390/s23010214
|View full text |Cite
|
Sign up to set email alerts
|

Step-Counting Accuracy of a Commercial Smartwatch in Mild-to-Moderate PD Patients and Effect of Spatiotemporal Gait Parameters, Laterality of Symptoms, Pharmacological State, and Clinical Variables

Abstract: Commercial smartwatches could be useful for step counting and monitoring ambulatory activity. However, in Parkinson’s disease (PD) patients, an altered gait, pharmacological condition, and symptoms lateralization may affect their accuracy and potential usefulness in research and clinical routine. Steps were counted during a 6 min walk in 47 patients with PD and 47 healthy subjects (HS) wearing a Garmin Vivosmart 4 (GV4) on each wrist. Manual step counting was used as a reference. An inertial sensor (BTS G-Walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…These non-wear periods were de ned as consistent low movement (low STD) across all acceleration axes for at least 30 minutes 51,52 . For each participant, we extracted data from four full (24-hour-long) days, as a recent study has shown that this duration provides reliable gait quantity measures 53 . Ten participants were excluded, due to an insu cient amount of activity (less than 96 hours of data), resulting in a nal number of 157 participants who were included in this stage.…”
Section: Stage 4: Assessing Construct Validitymentioning
confidence: 99%
“…These non-wear periods were de ned as consistent low movement (low STD) across all acceleration axes for at least 30 minutes 51,52 . For each participant, we extracted data from four full (24-hour-long) days, as a recent study has shown that this duration provides reliable gait quantity measures 53 . Ten participants were excluded, due to an insu cient amount of activity (less than 96 hours of data), resulting in a nal number of 157 participants who were included in this stage.…”
Section: Stage 4: Assessing Construct Validitymentioning
confidence: 99%
“…In PD, motor and gait manifestations could render step detection and step count challenging and hence significantly diminish the validity and reliability of device algorithms [20][21][22]. Nevertheless, a prior study from our group involving 47 PwPD demonstrated a strong criterion validity in step counting using a consumer smartwatch (Garmin Vivosmart 4), when worn on the side least affected by the disease and under well-controlled pharmacological conditions [20].…”
Section: Introductionmentioning
confidence: 95%
“…In PD, motor and gait manifestations could render step detection and step count challenging and hence significantly diminish the validity and reliability of device algorithms [20][21][22]. Nevertheless, a prior study from our group involving 47 PwPD demonstrated a strong criterion validity in step counting using a consumer smartwatch (Garmin Vivosmart 4), when worn on the side least affected by the disease and under well-controlled pharmacological conditions [20]. Similar results were obtained in real-life setting by Ginis and colleagues [23] who demonstrated the criterion validity in estimating average daily steps (avDS) of two Fitbit devices (Fitbit Alta and Fitbit Inspire 3) in 28 PwPD at home, compared to a research-grade device (Dynaport Movemonitor, McRoberts, NL).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations